Bacterial Artificial Chromosome-Based Experimental Strategies in the Field of Developmental Neuroscience - Terakawa, Youhei W.; Inoue, Yukiko U.; Asami, Junko; Inoue, Takayoshi (IntechOpen, 2011)
None